O delicado lugar do suicídio no noticiário impresso paraibano - Carvalho, Cláudia Maria de (2019)
Western societies have seen a significant increase in suicides. In Brazil, this problem has also been observed, especially among the young population. However, in the media, this is still a poorly addressed object. The present study identifies the objective and / or subjective factors by which journalism normally avoids the disclosure of cases of self-inflicted death, based on the premise still in the newsrooms of the press that the inclusion of facts related to suicides would influence the appearance of new cases. The research also includes a recovery throughout history of various perceptions of suicide, health authorities' recommendations regarding the care that the news should take not to incur "triggers" that encourage those with suicidal ideation. On the other hand, it addresses the influences of theoretical hypotheses of journalism such as gatekeeping, news value and the spiral of silence, as well as an analysis based on data collected in the only commercial printed newspaper of the state of Paraiba (Correio da Paraíba) in 2018, to identify how many cases and how self-inflicted death was recorded in the newspaper. This survey was obtained from the online version, in the editorials that correspond to the coverage of local facts. Finally, it makes use of semi-structured interviews with vehicle professionals to detect their thinking on the subject and whether there is an exhaustive guidance for the exclusion or direction of suicide-related material.